2015
DOI: 10.1186/s12989-016-0127-7
|View full text |Cite
|
Sign up to set email alerts
|

Multi-walled carbon nanotube induces nitrative DNA damage in human lung epithelial cells via HMGB1-RAGE interaction and Toll-like receptor 9 activation

Abstract: BackgroundCarbon nanotube (CNT) is used for various industrial purposes, but exhibits carcinogenic effects in experimental animals. Chronic inflammation in the respiratory system may participate in CNT-induced carcinogenesis. 8-Nitroguanine (8-nitroG) is a mutagenic DNA lesion formed during inflammation. We have previously reported that multi-walled CNT (MWCNT) induced 8-nitroG formation in lung epithelial cells and this process involved endocytosis. To clarify the mechanism of CNT-induced carcinogenesis, we e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 66 publications
1
40
0
Order By: Relevance
“…[60][61][62][63][64] In addition, TLR9 could recognize DNA, and is generally associated with HMGB1-DNA complex induced nucleotide immunity, while RAGE could amplify the TLR9dependent signal transduction cascade. [65][66][67] However, HMGB1-TLR9 promotes mitochondrial biogenesis in hepatocellular carcinoma to induce tumor growth mediated by hypoxia. 68…”
Section: Location Function Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…[60][61][62][63][64] In addition, TLR9 could recognize DNA, and is generally associated with HMGB1-DNA complex induced nucleotide immunity, while RAGE could amplify the TLR9dependent signal transduction cascade. [65][66][67] However, HMGB1-TLR9 promotes mitochondrial biogenesis in hepatocellular carcinoma to induce tumor growth mediated by hypoxia. 68…”
Section: Location Function Referencesmentioning
confidence: 99%
“…HMGB1-TLR9 could promote mitochondrial biogenesis in hepatocellular carcinoma to induce tumor growth mediated by hypoxia. 20,[60][61][62][63][64][65][66][67][68] TIM-3 Inhibits nucleic acid-mediated antitumor immunity in DCs. 19…”
Section: Ragementioning
confidence: 99%
“…It has recently been shown that MWCNT is incorporated into A549 cells via endocytosis, and leads to inflammatory reactions and induces RNOS . However, Hiraku et al demonstrate that MWCNT induces RNOS and 8‐nitro‐dG, but not in A549 cells, and indicate that the cell culture conditions may alter the balance of the generation of hydroxyl radicals and nitric oxide. It should be considered, therefore, that ROS‐originated and RNOS‐originated oxidative stresses are both involved in the (geno)toxicity of MWCNT and ENM in general.…”
Section: Discussionmentioning
confidence: 99%
“…The G to A transition is commonly observed in spontaneously‐occurring and chemically‐induced mutants, and the deamination of 5‐methylcytosine or the alkylation of guanine are its potential origin . Nitric oxide induces DNA damage by producing dinitrogen trioxide and then diazonium ions lead to the DNA deamination and 8‐nitro‐dG formation, and 8‐nitro‐dG preferentially causes the G:C to A:T transition through production of an apurinic site . However, nitric oxide is produced by activated macrophages in inflamed organs in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive ROS levels can trigger DNA strand breakage, 90 protein-peptide chain disruption, 91 lipid peroxidation 92 and other macromolecular damage, eventually leading to cell death. 93,94 The main targets of CNT cytotoxicity are cell membrane, lysosome, mitochondria, nucleus and cytoskeleton (such as actin). Damage to these structures induces loss of phagocytic ability, release of ROS, and injury to normal tissues.…”
Section: Energy-dependent Endocytic Pathwaysmentioning
confidence: 99%